Liver transplantation for portopulmonary hypertension responsive to targeted therapy. (March 2023) - Calleri, A.; Manuli, C.; Saracco, M.; Lavezzo, B.; Staiano, M.T.; Tandoi, F.; Panio, A.; Balagna, R.; Romagnoli, R.; Ottobrelli, A.; Martini, S.
Abstract : Background and Aims: In the current era of pulmonary arterial hypertension (PAH) therapy (tx), patients (pts) affected by liver disease with mild portopulmonary hypertension (POPH) can experience significant improvement after liver transplant (LT). We described characteristics of POPH pts who underwent LT in our Center. Methods: Among 1135 LT performed between 05/2013-05/2021 in our Center, we enrolled 10 cirrhotics with POPH. Diagnosis was made accordingto right heart catheterization (RHC) criteria: mean PA pressure(mPAP) >25 mmHg, PA wedge pressure(CAP)≤ 15 mmHg, pulmonary vascular resistance(PVR)>3WU. To achieve LT criteria (mPAP<35 mmHg, PVR<5 WU or mPAP 35-44 mmHg and PVR<3 WU) pts received phosphodiesterase-5-inhibitors(P-5i) and/or endothelin-receptor antagonists(ERA) and/or prostacyclin receptor-agonists. Follow-up was closed on 30/11/2022. Results: Recipients (Table 1 ): median age 53 years, 80% male, BMI 26Kg/m 2, 100% HCV cirrhosis, 20% HCC, 60% with large portosystemic-shunt, MELD 12. PAH-tx: pts#1-5 underwent ERA-tx; pts#6-8 ERA+P-5i; pt#9 and#10 prostacyclin+P-5i+ERA. Six pts (#1, #2, #4, #5, #9, #10) achieved POPH LT criteria after 4 mo of PAH-tx; 2 pts (#3, #6) after 8 mo, pt #8 after 12 mo.The 10 pts were transplanted after 0.3 y from registration on LT waiting list. Donors: median age 49 y, DRI 1.6. Post-LT: 3 pts developed early allograft dysfunction. All except pt #7 were extubated within day 2 post-LT; median hospital length of stay was 16 days. Pt#7 died after 18 days for cardiac failure.At a median follow-up of 2.9 y, 7 patients persistently discontinued PAH-tx. Conclusion: In our high-volume LT center, in the last 8 y we transplanted 10 cirrhotic pts affected by POPH and responsive to targeted therapy. LT offered a POPH resolution in 78% of the pts who were weaned off all PAH-tx without RHC evidence of POPH recurrence. One pt died early post-LT for cardiac failure. Careful patient and donor selection and proper timing of LT remain pivotal to obtain good outcomes.